Analisis Potensi Wisata Pantai Sebanjar Kecamatan Abal Kabupaten Alor 2023 - Yohanis Duil; Melki Imamastari Puling Tang; Petrus Mau Tellu Dony; Wanda rosiana Moulaa; Rumi Magdalena Tay (Yayasan Literasi Sains Indonesia, 2023)
Alor Regency is one of the regencies that has a lot of tourism potential and is also known as the land of a thousand mokos, therefore Alor is famous for its heaven in the east of the sun. According to the task obtained: This research was carried out in the village of Alor Besar Kec.ABAL with the title Analysis of the tourism potential of the Sebanjar beach. can spoil our eyes when we are there, the facilities that are offered are extraordinary where the local community organizes the tour very well. Sebanjar tourism looks crowded with visitors on holidays. On weekdays, visitors are not too crowded. To enter, visitors can pay a nominal fee of Rp. 2,000/person if seen from visitor data. Sebanjar beach tourism also provides facilities for visitors if they want to stay where there are eight villas. And there is also a cafe that provides typical food.